Labour Market Entry Conditions, Wages and Job Mobility - Ronald Bachmann; Thomas K. Bauer; Peggy David (Rheinisch-Westfälisches Institut für Wirtschaftsforschung (RWI), 2010)
Economic conditions at the time of labour market entry can induce wage differentials between workers entering the labour market at different points in time. While the existence and persistence of these entry wage differentials are well documented, little is known about their interaction with employees' mobility behaviour. This paper contributes to this research area by analyzing the interaction between job mobility and entry wage differentials using German administrative data. The results suggest that labour market entrants earning less than the average starting wage are more likely to change jobs, directly from employer to employer as well as indirectly via an unemployment spell. In addition they are more likely to change occupation. Moreover, job mobility tends to reduce the effects of labour market entry conditions, implying that job mobility operates as an adjustment mechanism that mitigates entry wage differentials. These results hold not only for high-skilled, but also for medium-skilled and unskilled workers. – – Die beim Arbeitsmarkteintritt vorherrschenden wirtschaftlichen Bedingungen können zu Lohndifferentialen zwischen Arbeitnehmern, die zu unterschiedlichen Zeitpunkten in den Arbeitsmarkt eintreten, führen. Dieses Papier analysiert die Interaktion zwischen diesen Lohndifferentialen und der Mobilität von Arbeitnehmern unter Verwendung von administrativen Daten für Deutschland. Die Ergebnisse zeigen, dass Arbeitnehmer, die bei Arbeitsmarkteintritt weniger als den durchschnittlichen Einstiegslohn verdienen, eine höhere Jobwechselwahrscheinlichkeit aufweisen, sowohl bezüglich direkter (Job-zu-Job) Wechsel als auch indirekter (durch den Zustand der Arbeitslosigkeit hindurch) Jobwechsel. Sie haben zudem eine höhere Wahrscheinlichkeit, den Beruf zu wechseln. Darüber hinaus verringert Mobilität die Auswirkungen der beim Arbeitsmarkteintritt vorherrschenden wirtschaftlichen Bedingungen und fungiert somit als ein Anpassungsmechanismus, der Lohndifferentiale von Arbeitsmarkteinsteigern abschwächt.
Keywords: E24; J31; J62; J64; 330; Mobility; job-to-job; wages; labour market entry; initial conditions; Berufseinstieg; Lohnstruktur; Arbeitsmobilität; Schätzung; Deutschland